Repertoar samospeva na Slovenskem ali/in slovenskega samospeva 19. stoletja v fonoteki-glasbenem arhivu Radia Slovenija in njegovi izvajalci - Križnar, Franc (Muzikološki zbornik, 2006)
The article gives a minute survey and analysis of the archival sound material regarding 19th century Slovene creativity in the solo song genre, as preserved in the archives of RTV Slovenia, thus shedding important light on its reception in the second half of the 20th century.
Keywords: 19.st.; glasba; glasbeni arhivi; music; samospev; Slovenia; Slovenija